THE DIVIDE BETWEEN POLICY AND PRACTICE IN EFL HIGH SCHOOL CLASSROOMS IN JAPAN - Bartlett, Kevin (PEOPLE: International Journal of Social Sciences, 2017)
This paper examines the current high school English language curriculum guidelines established by the Ministry of Education, Culture, Sport, Science and Technology (MEXT) in Japan, and the teaching approaches that are most prevalent in Japanese high school EFL classrooms by examining the implementation of the curriculum in the classroom. Results obtained from surveys, semi-formal interviews, and informal conversations with English language teachers at high schools in Kyushu and Hyogo, Japan, provide an overview of teaching styles and practices within classrooms, which differ to the approaches recommended by policy. Based on this evidence, the paper will explore what cultural and organizational factors are hindering the incorporation of Communicative Language Teaching (CLT) approaches in the classroom by using a conceptual framework based on Hofstede’s Large Culture.